2017
DOI: 10.5958/0974-181x.2017.00011.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Esterified Glucomannan on the Performance of Broiler Chickens During Experimental Aflatoxicosis

Abstract: Wade, M.R. and Sapcota, D. 2017. Effect of dietary esterified glucomannan on the performance of broiler chickens during experimental aûatoxicosis. Animal Nutrition and Feed Technology,.The amelioration effect of dietary esterified glucomannan (EGM) was studied in experimental aflatoxicosis using broiler chickens. Day-old chicks (n=270) were divided into 6 treatment groups, containing 45 numbers in each and the study was made in triplicates for 6 weeks. A control ration was prepared with conventional feedstuffs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
3
1
0
Order By: Relevance
“…The incorporation of aflatoxins in chickens at a dose rate of 2 mg/kg resulted in reduction in body weight gain by 20–30% [ 19 ]. Similar results were also reported by [ 20 , 21 , 22 ]. When the Lactobacillus plantarum was used in combination with aflatoxins, it improved the feed intake and body weight.…”
Section: Discussionsupporting
confidence: 92%
“…The incorporation of aflatoxins in chickens at a dose rate of 2 mg/kg resulted in reduction in body weight gain by 20–30% [ 19 ]. Similar results were also reported by [ 20 , 21 , 22 ]. When the Lactobacillus plantarum was used in combination with aflatoxins, it improved the feed intake and body weight.…”
Section: Discussionsupporting
confidence: 92%
“…The impairment of metabolizing capability may be the cause of AFB1's negative influence on growth parameters [ 27 ]. These findings are in harmony with previous studies reporting the negative effects of aflatoxin on growth performance [ 5 , 21 , 28 ]. Moreover, Mahrose et al [ 29 ] reported the deleterious effects of aflatoxin on the growth performance of Japanese quail.…”
Section: Discussionsupporting
confidence: 92%
“…Supplementing diets with yeast cell walls increases weight gains and improves feed conversion [ 20 ]. A trial of using a cell wall of yeast to minimize the adverse effects of aflatoxin-contaminated diets in broiler chicks resulted in a significant increase in BW gain and improved feed consumption [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of serum AST and GGT were observed in birds receiving 0.5 ppm of AF as compared to control group chickens, indicating considerable damage to the liver. Similar findings of elevated activities of serum enzymes due to aflatoxicosis were observed by many researchers [25][26][27]). Raju and Devegowda (2000) recorded no difference in AST levels in birds fed AF up to 0.3 ppm for 21 days [25].…”
Section: Discussionsupporting
confidence: 88%